Influence of Indium Tin Oxide (ITO) poling temperature in vacuum on surface roughness of Polyvinylidene Fluoride(PVDF) film - Suprapto, Suprapto; Lisyanto, Lisyanto; Eswanto, Eswanto; Riadi, Selamat; Gunawan, Safri; Iskandar, Henry; Jubaidah, Jubaidah; Muhtadin, Muhtadin (Politeknik Negeri Lhokseumawe, 2023)
The surface roughness is a significant parameter of the performance of PVDF thin film sensors. In this work, we have investigated the effect of ITO poling in vacuum at various temperature on the surface roughness of uniaxially stretched PVDF film. The influence of poling temperature on the surface roughness of PVDF film was examined using atomic force microscopy (AFM). In this work, the AFM data are obtained through the database, and topography is analyzed using Gwydion Software (GS). GS has characterized surface roughness in terms of Average Roughness (Ra), Root Mean Square (Rrms), and Arithmetic average height (Rz). The results show that the GS can detect and measure profile thickness and roughness on a nanoscale with reliable accuracy. The results confirm that the increased poling temperature can reduce the roughness of the surface.